Broodstock development and captive maturation of hilsa (Tenualosa ilisha) in a brackishwater pond‐based system. Issue 3 (4th August 2020) - De, Debasis; Shyne Anand, Panantharayil S.; Mukherjee, Suchita; Kumar, Prem; Dayal, Jagabathula Syama; Raja, Ramalingam Ananda; Bera, Aritra; Suresh, Vettath Raghavan; Vijayan, Koyadan Kizhakedath
Abstract: Successful captive broodstock development of clupeid fish, hilsa, is one of the major challenges for the artificial propagation of this economically valued fish. The present study provides novel insights into the pond‐reared captive broodstock development of hilsa using artificial feed. In the present study, wild collected hilsa fry (weight 1.35 ± 0.13 g, length 53.84 ± 0.95 mm) were reared in grow‐out ponds for 6 months followed by maintaining them as broodstock in other ponds using formulated feed in both cases. After 6 months of pond rearing, the average body weight and length of fish were 66.76 ± 4.53 g and 184.75 ± 3.65 mm, respectively. In broodstock ponds, hilsa subadults fed with formulated feed (crude protein 41.06%) ensured significant advancement in ovarian maturity with gonado somatic index of 9.09%, enhanced secondary yolk stage oocytes of 91.66% and enlargement of oocyte diameters up to 570 μm. The broodstock reached somatic growth such as average body weight and average body length of 383.80 ± 27.38 g and 339.33 ± 9.68 mm, respectively, with a condition factor of 1.06 ± 0.15. Gut content analysis revealed the better acceptability of the artificial feed. Lipid profiling of muscle and ovary during gonadal maturation revealed mobilization of fat from muscle to ovary and selective retention of some fatty acids ( i.e., C14:0, C18:0, C20:5, C22:6 and C20:4) in the ovary, which might help in gonadal maturation. Statement of Significance: Successful rearing of wild‐caught hilsa juvenile in captive condition using formulated feed showed its potential as aquaculture species in low saline conditions. Advance stage of maturation in low saline captive conditions showed the possibility for induced breeding of hilsa, a high priced anadromous fish. Mobilization of fat from muscle to ovary and selective retention of some fatty acids in the ovary showed the scope of dietary manipulation for broodstock development of hilsa.